2008
DOI: 10.1103/physreva.77.032716
|View full text |Cite
|
Sign up to set email alerts
|

Cross sections for short-pulse single and double ionization of helium

Abstract: In a previous publication, procedures were proposed for unambiguously extracting amplitudes for single and double ionization from a time-dependent wavepacket by effectively propagating for an infinite time following a radiation pulse. Here we demonstrate the accuracy and utility of those methods for describing two-photon single and one-photon double ionization of helium. In particular it is shown how narrow features corresponding to autoionizing states are easily resolved with these methods.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 28 publications
2
57
0
Order By: Relevance
“…The long-range interaction between the ionized electron and the residual ion in the exit channel contains now both a Coulombic and a dipolar interaction, = − ⃗ ⃗/ 3 . Their direct contributions to EWS in the absence of a streaking field is fully included in the exact calculation of the dipole transition matrix for single ionization of He employing exterior complex scaling (McCurdy et al, 2004;Palacios et al, 2008Palacios et al, , 2009Liertzer et al, 2012). In the presence of a streaking field, however, both long-range portions give additional contributions.…”
Section: Time-resolved Photoionization Of Many-electron Atomsmentioning
confidence: 99%
“…The long-range interaction between the ionized electron and the residual ion in the exit channel contains now both a Coulombic and a dipolar interaction, = − ⃗ ⃗/ 3 . Their direct contributions to EWS in the absence of a streaking field is fully included in the exact calculation of the dipole transition matrix for single ionization of He employing exterior complex scaling (McCurdy et al, 2004;Palacios et al, 2008Palacios et al, , 2009Liertzer et al, 2012). In the presence of a streaking field, however, both long-range portions give additional contributions.…”
Section: Time-resolved Photoionization Of Many-electron Atomsmentioning
confidence: 99%
“…Comprehensive numerical studies on the DI of helium following the absorption of a few XUV photons were carried out by Parker et al [16] starting 15 years ago. Following the 2005 experiment of Hasegawa et al [7], two-photon DI of helium has been the subject of several theoretical studies [15,[17][18][19][20][21][22][23][24][25][26][27][28]. In particular, Zhang et al [26] calculated joint angular distributions (JADs) for two-photon DI by XUV pulses in both the nonsequential (39.5 eV < ω XUV < 54.4 eV) and the sequential ( ω XUV > 54.4 eV) regimes for different energy sharings of the emitted electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Soon afterwards, Briggs and coworkers derived selection rules for helium DI, emphasizing their relevance for the understanding of photoelectron angular distributions [1,[11][12][13][14]. The convergent close-coupling (CCC) calculations by Keifets and Bray [6], TDCSs calculated by Huetz et al [6,10], as well as TDCSs obtained from timedependent close-coupling (TDCC) simulations by Palacios et al [15] were found to be in good agreement with the angular distributions in the absolute TDCSs for the DI of helium by 99 eV XUV photons measured by Bräuning et al [6]. Comprehensive numerical studies on the DI of helium following the absorption of a few XUV photons were carried out by Parker et al [16] starting 15 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…It is enabled by strong electronic correlation and thus clearly distinct from the sequential double-ionization mechanism. Nonsequential double ionization was observed for noble gas atoms in 1982 [2] and received rapidly increasing attention from both experimentalists [3-9] and theorists [10][11][12][13].…”
mentioning
confidence: 99%
“…It is enabled by strong electronic correlation and thus clearly distinct from the sequential double-ionization mechanism. Nonsequential double ionization was observed for noble gas atoms in 1982 [2] and received rapidly increasing attention from both experimentalists [3-9] and theorists [10][11][12][13].Photoelectron angular distributions of single-photon double ionization were found to owe their structure partly to (dipole) selection rules [11,14,15] and to consist of symmetrical and antisymmetrical contributions (with regard to electron exchange), that each can be written as the product of an angular and a correlation factor [11]. For coplanar emission geometry, where the emitted-electron momenta and polarization axis of the linearly polarized extremeultraviolet (XUV) pulse lie in a plane, and for equal energy sharing (equal asymptotic kinetic energies E 1 and E 2 of the photoelectrons), the angular factor becomes j cos θ 1 þ cos θ 2 j 2 , where θ 1 and θ 2 are photoelectron emission angles relative to the polarization direction of the ionizing light, while the electron correlation factor follows as expf−4 ln 2½ðθ 12 − πÞ=θ 1=2 2 g, with the mutual emission angle θ 12 ¼ jθ 1 − θ 2 j.…”
mentioning
confidence: 99%